Cyclo Application / Obrain Mang … [et al.] - Mang, Obrain; Halid, Mohd. Zuqhairy Khan; Kimpong, Jilhelson; Mohd. Hardy, Mohd. Arsy Ardy (Faculty of Computer and Mathematical Sciences, 2022)
Every day, 364,000 bicycles are made and 47,670 are sold. Bicycles are created at double the pace of cars. Every year, it is estimated that around 15 million bicycles are dumped by their owners. This had led to many discarded bikes wind up in landfills (Ruiz, 2020). To deal with this issue, we have come up with an application called Cyclo. It is a bicycle rental app which acts as a transportation medium for tourist and non-tourist to stroll around the city especially to the local tourist attraction and they can also stop-by at the hawkers to enjoy local street foods which also helps boost the local economy. The objectives of Cyclo are 1) to assist local small and medium-sized enterprises (SME) boosts their income by renting their bicycle (bicycle owners or personal), 2) to reduce the bicycle trivial landfill (oversupplies and unused bicycle), and 3) to promotes sustainable tourism among tourist and non-tourist. The novelties of Cyclo are to promotes small and medium-sized enterprises (SME), minimize the number of unused bicycles, and promotes sustainable tourism among tourist and non-tourist. This application brings an impact on 1) economy, it helps the local small and medium- sized enterprises (SME) will gain more income, 2) social, it will educate the tourist and non-tourist on local tourist attractions and local cuisines, and 3) environment, it will reduce the land pollution and carbon footprints. Lastly, the potential commercialization can be seen in the global bike sharing market was valued at $3.43 billion in 2019 and is expected to reach $6.98 billion by 2027, growing at a 14.0% CAGR between 2020 and 2027. From here, we can acknowledge that the global bike sharing market are increasing year-by-year as the usage of smartphones and applications for travelling is proceeding.